Application of cold compress of Traditional Chinese Medicine in a patient with wind-warm and pulmonary heat syndrome (中药冷敷技术在1例风温肺热病患者中的应用) - ZHOU Jie (周洁); CHEN Hong (陈宏); WANG Huaxin (王华新); SHU Baozhen (舒宝珍); TANG Ling (唐玲) (Association of Integrative Nursing, 2022)
This paper summarized the application effect of cold compress of Traditional Chinese Medicine (TCM) in a patient with wind-warm and pulmonary heat syndrome. According to the outcomes of nursing evaluation and diagnosis, the TCM cold compress therapy was carried out in combination with nursing interventions such as daily care, nutrition guidance, emotion nursing, and so on. The TCM cold compress therapy has obvious effect on body cooling during fever caused by wind-warm and pulmonary heat syndrome, and it demonstrates the characteristics of easy-to-use, convenience and cost-effectiveness. (本文总结中药冷敷技术在1例风温肺热病患者中的应用效果。结合护理评估和诊断结果, 给予患者中药冷敷技术, 同时配合生活起居、饮食、情志等护理干预措施。在常规治疗基础上, 中药冷敷技术降温效果明显, 体现了中医护理技术"简、验、廉、效"的特点。)